Analysis of the start-up mechanism of moraine debris flow based on flume test:A case study of the Aierkuran Gully along the Sino-Pakistan highway - Yuanyuan FAN; Ling SONG; Xueli WEI (Zhongguo dizhi zaihai yu fangzhi xuebao, 2021)
Debris flow caused by moraine soil startingis very common along the Sino-Pakistan Highway, but in previous studies, the characteristics of moraine soil and its influence on the formation of glacier debris flow is lacking. In order to further explore the causes of debris flow burst, based on flume test, the process and mechanism of debris flow caused by moraine soil starting in the study area are discussed in connection with the characteristics of moraine soil in the study area. The results show: (1) when the flow rate of molten water is 8 L/min, 12 L/min, 16 L/min and 56 L/min, the internal structure of moraine soil changes, and the failure form and starting process of moraine soil are different. (2) The sediment chargecontent fluctuates with the change of melt water flow and time, and the debris flow scour start and the soil collapse silt in repeated circulation. (3) Based on the characteristics of moraine soil and experimental phenomena, the starting mechanism of glacier debris flow is divided into three parts: osmotic saturation, erosion collapse and scour starting. (4) The stability coefficient of the ice-and-soil debris flow is a power-function relation with the flow of water.